The Role of Toll-Like Receptor 2 in Inflammation and Fibrosis during Progressive Renal Injury - Leemans, Jaklien C.; Butter, Loes M.; Pulskens, Wilco P. C.; Teske, Gwendoline J. D.; Claessen, Nike; van der Poll, Tom; Florquin, Sandrine (PloS one, 2009)
Tissue fibrosis and chronic inflammation are common causes of progressive organ damage, including progressive renal disease, leading to loss of physiological functions. Recently, it was shown that Toll-like receptor 2 (TLR2) is expressed in the kidney and activated by endogenous danger signals. The expression and function of TLR2 during renal fibrosis and chronic inflammation has however not yet been elucidated. Therefore, we studied TLR2 expression in human and murine progressive renal diseases and explored its role by inducing obstructive nephropathy in TLR2(-/-) or TLR2(+/+) mice. We found that TLR2 is markedly upregulated on tubular and tubulointerstitial cells in patients with chronic renal injury. In mice with obstructive nephropathy, renal injury was associated with a marked upregulation and change in distribution of TLR2 and upregulation of murine TLR2 danger ligands Gp96, biglycan, and HMGB1. Notably, TLR2 enhanced inflammation as reflected by a significantly reduced influx of neutrophils and production of chemokines and TGF-beta in kidneys of TLR2(-/-) mice compared with TLR2(+/+) animals. Although, the obstructed kidneys of TLR2(-/-) mice had less interstitial myofibroblasts in the later phase of obstructive nephropathy, tubular injury and renal matrix accumulation was similar in both mouse strains. Together, these data demonstrate that TLR2 can initiate renal inflammation during progressive renal injury and that the absence of TLR2 does not affect the development of chronic renal injury and fibrosis.